Efektivitas Badan Permusyawaratan Desa dalam Pengawasan Penyelenggaraan Pemerintah Desa di Desa Tegal Kertha Kecamatan Denpasar Barat Kota Denpasar - Putu Astawa, I Gusti Lanang; Winaya, I Ketut; Purnamaningsih, Putu Eka (CITIZEN CHARTER, 2020)
ABSTRACT Village Consultative Body (BPD) Tegal Kertha is a village legislative institution whose members are selected by the community directly to overseeing performance village head to realize transparency and accountability governance villages. The purpose of this research to see extent to which effectiveness Village Consultative Body (BPD) Tegal Kertha in the process supervision gavornment village in accordance with the stated goals and plans. Measurement effectiveness uses the Gibson theory with 3 variables that affect the level of effectiveness of an organization with based on goals approach, system based approach, and stakeholders based approach is to look preventive supervision and supervision of repressive by Situmorang. The result of this research indicate Village Consultative Body (BPD) Tegal Kertha carry out function well but there are still found as the weakness of the management of community aspiration and increase knowledge awareness of the tehnically train them about their function and tasks. Keywords: Effectiveness, Village Consultative Body (BPD), Supervision, government village.